PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KEPUASAN KERJA KARYAWAN PT PATRA BADAK ARUN SOLUSI - Fanisya Rahmadina Putri (2021)
This quantitative research aims to determine and prove the effect of Compensation, Work Environment, and Organizational Citizenship Behavior (OCB) on Employees Job Satisfaction at PT Patra Badak Arun Solusi. The sampling technique used is probability sampling with a simple random sampling approach using the Slovin formula so that a sample of 96 employees is obtained. Data was collected through the distribution of questionnaires. The data analysis technique used is the Partial Least Square (PLS) method. Results obtained in this research (1) compensation has a positive and significant effect on job satisfaction, (2) the work environment has a positive and significant effect on job satisfaction, (3) organizational citizenship behavior (OCB) has a positive and significant effect on job satisfaction.